PENINGKATAN NILAI TAMBAH HASIL IKAN SEBAGAI STRATEGI PENGEMBANGAN EKONOMI LOKAL DI PULAU HARAPAN, KEPULAUAN SERIBU - Dewi Widowati Hermajiwandini, Chandra Murti Dewi; Pradana, Hasta Dwi; Lestari, Dwi Ayu; Afaqa Hudaya; Saputro, Dio Bimo (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Coastal fishers in small island areas commonly face low value-added conditions due to heavy dependence on selling fresh fish. From a development economics perspective, this situation reflects weak downstream processing and limited local economic diversification. This Community Service Program aimed to increase the value added of fish products through hands-on training in salted fish processing as a simple and applicable post-harvest activity. The program was conducted offline on Harapan Island, Seribu Islands, on September 26, 2025, involving 37 fishers. The method began with a short theoretical session on value added and local economic development, followed by practical training on salting and sun-drying techniques. The results showed high participant enthusiasm and improved knowledge and practical skills in fish processing. This activity contributes to strengthening local economic development and enhancing the economic capacity of coastal fishing communities.